2018
DOI: 10.1038/s41388-018-0163-x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of HTLV-2 antisense protein is controlled by PML nuclear bodies in a SUMO-dependent manner

Abstract: Since the identification of the antisense protein of HTLV-2 (APH-2) and the demonstration that APH-2 mRNA is expressed in vivo in most HTLV-2 carriers, much effort has been dedicated to the elucidation of similarities and/or differences between APH-2 and HBZ, the antisense protein of HTLV-1. Similar to HBZ, APH-2 negatively regulates HTLV-2 transcription. However, it does not promote cell proliferation. In contrast to HBZ, APH-2 half-life is very short. Here, we show that APH-2 is addressed to PML nuclear bodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Similar to HBZ, APH-2 inhibited Tax-2-induced NF-κB activity, but unexpectedly and unlike Tax-1, high expression of Tax-2 did not restore the activation of NF-κB (Figure 2B). Of note, this inhibitory effect of APH-2 was evident despite the fact that APH-2 was less expressed than HBZ in transfected cells, as previously reported (Panfil et al, 2016; Dubuisson et al, 2018). Because APH-2 appeared to be more potent than HBZ in the inhibition of Tax-mediated NF-κB activation, the effect of HBZ and APH-2 expression on the NF-κB promoter activation mediated by p65 over-expression was then compared in HEK293T cells.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Similar to HBZ, APH-2 inhibited Tax-2-induced NF-κB activity, but unexpectedly and unlike Tax-1, high expression of Tax-2 did not restore the activation of NF-κB (Figure 2B). Of note, this inhibitory effect of APH-2 was evident despite the fact that APH-2 was less expressed than HBZ in transfected cells, as previously reported (Panfil et al, 2016; Dubuisson et al, 2018). Because APH-2 appeared to be more potent than HBZ in the inhibition of Tax-mediated NF-κB activation, the effect of HBZ and APH-2 expression on the NF-κB promoter activation mediated by p65 over-expression was then compared in HEK293T cells.…”
Section: Resultssupporting
confidence: 83%
“…pEF-p52 was kindly provided by Dr. Matsuoka. pcDNA3-VSV-APH-2, pSG5M-Tax2-His, His-HBZ have been previously described (Journo et al, 2013; Dubuisson et al, 2018). pSpCas9(BB)-2A-Puro (PX459) V2.0 vector was purchased from Addgene.…”
Section: Methodsmentioning
confidence: 99%
“…This conclusion was supported by our data showing that bafilomycin, a lysosomal inhibitor, also stabilized APH-2 expression. Although lysosomal degradation of APH-2 has not been reported previously, APH-2 has been shown to be degraded by the proteasome following its SUMOylation (45). Overall, our data support the view that, in addition to the proteasome, APH-2 is degraded by the lysosomal pathway.…”
Section: Discussionsupporting
confidence: 86%
“…We also found that APH-2 is more effective than HBZ in inhibiting NF-κB activation by Tax, and we proposed a model in which the recruitment of APH-2 in cytoplasmic structures with NF-κB factors may inhibit p65's nuclear translocation, leading to NF-κB inhibition [105]. Another property of APH-2 that distinguishes it from HBZ is its targeting to PML nuclear bodies, which leads to proteasomal degradation of APH-2 in a SUMO-dependent manner [123].…”
Section: Deregulation Of Nf-κb Activation By Hbzmentioning
confidence: 99%